A Profile of Digital Literacy, Problem-Solving Skills, and Socio-Cultural Awareness Among Pre-Service Biology Teacher in Bali - Sudirgayasa, I Gede; Sulisetijono; Mahanal, Susriyati; Gofur, Abdul; Dewi, Ni Putu Sri Ratna; Ratnani, Dewa Ayu Sri; Rai, I Gusti Ayu; Sudiana, I Made (Journal of Science and Education Research, 2025)
This study aims to identify the levels of digital literacy, problem-solving skills, and socio-cultural awareness among prospective biology teachers. A cross-sectional survey method was employed. Data were collected through the distribution of a closed-ended questionnaire on February 10, 2023. The questionnaire used a Likert scale, with each item scored on a range from 1 to 5. The digital literacy questionnaire consisted of 20 items, the problem-solving skills questionnaire comprised 24 items, and the socio-cultural awareness questionnaire included 15 items. The questionnaires were distributed to biology education students from four universities in Bali: Universitas Pendidikan Ganesha, Universitas Mahasaraswati Denpasar, Universitas PGRI Mahadewa Indonesia, and IKIP Saraswati. Respondents were selected using purposive sampling, based on specific criteria relevant to the research objectives. The research instruments were developed based on the aspects and indicators of 21st-century skills proposed by Greenstein. The collected data were then analyzed descriptively to address the research questions. The findings of the study are as follows: students' digital literacy falls within the intermediate category; their problem-solving skills are at the basic level; and their socio-cultural awareness is also categorized as intermediate. It is necessary to develop alternative learning programs that enhance students' digital literacy, problem-solving abilities, and socio-cultural awareness. One potential approach is project-based learning that directly integrates technology use and addresses real-life issues at both local and global levels.